2009
DOI: 10.1088/0004-637x/709/1/88
|View full text |Cite
|
Sign up to set email alerts
|

Fake Star Formation Bursts: Blue Horizontal Branch Stars Masquerade as Young Massive Stars in Optical Integrated Light Spectroscopy

Abstract: Model color-magnitude diagrams of low-metallicity globular clusters (GCs) usually show a deficit of hot evolved stars with respect to observations. We investigate quantitatively the impact of such modeling inaccuracies on the significance of star formation history reconstructions obtained from optical integrated spectra. To do so, we analyze the sample of spectra of galactic globular clusters of Schiavon et al. with STECKMAP (Ocvirk et al.), and the stellar population models of Vazdekis et al. and Bruzual & Ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 60 publications
6
49
0
2
Order By: Relevance
“…The STARLIGHT fits do indicate a small contribution (0.1% by mass) of young stars in the nucleus, but these are almost certainly old blue stars that are not well accounted for by current evolutionary synthesis models (Koleva et al 2008;Cid Fernandes & González Delgado 2010). The weakness of Hα reinforces the conclusion that these are "fake bursts" as described by Ocvirk (2010), otherwise EW(Hα) should be much stronger. As discussed above, our energetic balance approach indicates that an additional excitation mechanism other than pABG stars might operate at large radii (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The STARLIGHT fits do indicate a small contribution (0.1% by mass) of young stars in the nucleus, but these are almost certainly old blue stars that are not well accounted for by current evolutionary synthesis models (Koleva et al 2008;Cid Fernandes & González Delgado 2010). The weakness of Hα reinforces the conclusion that these are "fake bursts" as described by Ocvirk (2010), otherwise EW(Hα) should be much stronger. As discussed above, our energetic balance approach indicates that an additional excitation mechanism other than pABG stars might operate at large radii (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…The Salpeter IMF is adopted. Like the other bases discussed next, GM does not adequately cover the blue horizontal branch, both because it does not reach very low Z and because, as thoroughly discussed by Ocvirk (2010), these models perform poorly in this phase anyway.…”
Section: Ssp Spectral Modelsmentioning
confidence: 94%
“…Rotation in massive stars (Levesque et al 2012), rapid phases during the post-main-sequence evolution of intermediate-mass stars (Maraston 2005), and binarity (Li et al 2013) are examples of phenomena that affect the radiative output of stellar populations, but are still at the forefront of research, and thus prone to uncertainties. A practical example of how incomplete treatment of evolutionary phases affects spectral synthesis analysis is discussed by Koleva et al (2008), Cid Fernandes &Ocvirk (2010). Using different codes, these studies found that spectral synthesis of old Milky Way and LMC globular clusters suggests the presence of very young stellar populations accounting for some 10-20% of the optical light, an astrophysically absurd result that also happens in some old, "red and dead" galaxies (Cid Fernandes et al 2011).…”
Section: Uncertainties Associated To Evolutionary Synthesis Models: Amentioning
confidence: 99%
See 1 more Smart Citation
“…Significant differences (p < 0.05 in the AD and MW tests) occur only at log t ≤ 7.3 for the 15.8 ≤ log R < 16.8 bin, and at 9.7 ≤ log t ≤ 9.8 for the log R ≥ 16.8 bin. However, the upturn for RL at ages log t < 7.5 is probably artificial and should be disregarded (see the discussion on blue horizontal branches stars in stellar population models in Ocvirk 2010 andStasińska et al 2015). The difference at large ages in the bin log R ≥ 16.8 is noticable only in the last two age bins.…”
Section: Comparison Of the Properties Of Matched Rl And Rq Samplesmentioning
confidence: 99%